Unaided Vision after Manual Suture Less Small Incision Cataract Surgery (MSICS) - Abdul Munim Khan (Journal of Rawalpindi Medical College, 2013)
Background: To assess the efficacy of manual small incision cataract surgery (MSICS) by recording unaided vision four weeks after surgery. Methods: In this case control study, patients who underwent manual small incision cataract surgery were registered. After surgery they were followed for four weeks.Manual small incision cataract surgery (MSICS) with implantation of a rigid, single piece Poly Methyl Meth Acrylate PCIOL (Posterior Chamber Intra Ocular Lens) 5.25 mm Fred Hallows Foundation, was performed , under local anesthesia. Patients were followed up on first post operative day, then at 2 weeks and finally at four weeks. At four weeks the unaided vision was especially recorded Results: Majority (89.7 %) of the patients attained good unaided post operative vision. Majority (62.7%) had excellent vision post operatively (6/6-6/9). Surgically induced astigmatism (SIA) was 0.12 Diopters post operatively . None of the patients had poor vision and majority (90%) had good unaided vision Conclusion: MSICS is an acceptable option for high volume cataract surgery in developing countries like Pakistan.